Embeddings into countably compact Hausdorff spaces - Banakh, Taras; Bardyla, Serhii; Ravsky, Alex (Ukrains’kyi Matematychnyi Zhurnal, 2023)
UDC 515.122We consider the problem of characterization of topological spaces  embedded into countably compact Hausdorff topological spaces. We study the separation axioms for subspaces of Hausdorff countably compact topological spaces and construct an example of a regular separable scattered topological space that cannot be embedded into a Urysohn countably compact topological space.